The effect of an aspalathin-rich rooibos extract on inflammatory crosstalk between adipocytes and muscle cells - Obonye, Nnini (Stellenbosch : Stellenbosch University, 2021, 2021)
Thesis (MSc)--Stellenbosch University, 2021